Estimating avoidable burden of stillbirth attributable to greenness improvement in Iran - Yang Yuan; Fatemeh Mayvaneh; Yaqi Wang; Jixing Yang; Yunquan Zhang; Fang Shi (Ecotoxicology and Environmental Safety)
Introduction: Expanding evidence suggests beneficial impacts of greenspace on human health, yet the relationships between greenness and stillbirth remain unknown. This study aimed to quantify the risk and burden of stillbirth associated with maternal greenness exposure during pregnancy. Methods: A total of 3,982,304 eligible birth records across 31 provinces in Iran from 2013 to 2018 were included in this study. Greenness exposure during pregnancy was assessed using the satellite-based normalized difference vegetation index (NDVI) and enhanced vegetation index (EVI) with multiple buffers. Stillbirth was defined as the birth of babies with no signs of life at ≥22 weeks of gestation. Multivariable-adjusted logistic regression models were employed to investigate greenness-stillbirth associations. To estimate the exposure-response functions, greenness exposures were fitted as smooth terms using restricted cubic splines. Avoidable burden of stillbirth under the predefined scenarios of improved greenness was estimated through a counterfactual analysis. Results: A total of 29,770 stillbirths occurred during 2013–2018, totaling to an overall annual rate of 748 cases per 100,000 births. Lower stillbirth risks were consistently seen in pregnant mothers being exposed to greater greenness within buffers of 500–3000 m. For instance, per 0.1-unit increase of NDVI and EVI within a 3000-m buffer was associated with the estimated odds of 0.971 (95 % confidence interval: 0.963–0.978) and 0.957 (0.947–0.968) for stillbirth, respectively. Evidently nonlinear relationships were identified between greenness exposure and stillbirth, exhibiting approximately an inverted L-shaped pattern with the steeper slope at high greenness levels. Assuming causality, 34–41 stillbirths per 100,000 births could be avoidable by achieving the 80th percentile of NDVI/EVI during 2013–2018, representing 4.6–5.4 % of nationwide registry-based stillbirths in Iran. Conclusions: Our findings provided robust national evidence on beneficial effects of surrounding greenness in alleviating risk and burden of stillbirth in Iran, suggesting a greener environment could potentially serve as a promising intervention strategy for reducing stillbirth risk in less developed countries.